Religijność w Księdze Kapłańskiej - Stanek, Teresa (Wydział Teologiczny UAM, 2009)
The Book o f Leviticus appears as a compilation o f fragmentary cultic and ethical prescriptions, coming from different periods o f religious history o f Israel. The synchronic analysis, started by Mary Douglas, proved that the editor o f final version o f Leviticus was a great artist, with a religious goal. Leviticus is a book that presents multiple layers o f meaning. In this article the Book of Leviticus was considered from the Religionswissenschaft point o f view. The text was divided on a major blocks according to its theme, and then asked what message was delivered through each one o f them; and subsequently, what was message o f the whole Book. Careful analysis of vocabulary, as well as the time and place o f action, allow to suggest a new structure - the four final chapters might serve as the endings for three blocks o f text. The theme leads the reader from the temple to the community; from the present to the future.
Religiousness in the Book of Leviticus
Keywords: Leviticus; religion of Israel; symbolism; synchronic analysis